Factors That Influence the Low Rate of Structural Funds Absorbtion in Romania - Corina Berica (CES Working Papers, 2010)
In the Strategic report for 2010 concerning the application of the programmes for the period 2007 – 2013, it can be observed that Romania is situated on the penult place regarding the allocation of the amounts for the selected projects, with a percent of 14% comparing to the EU average of 27,1%. This low rate generates a series of questions: “why?”, “who is responsible?” This considerable gap is sustained by several internal and external factors, which block us from having encouraging results: internal factors, at the beneficiary's level and external factors, at the level of the institutions responsible with supervising and implementing the projects. With this essay, by identifying the factors which influence the absorption rate of the Structural Funds in Romania, we intended to make a first step in solving this problem, which requires a special attention.
Keywords: 330; Structural Funds; absorption rate; financial contribution; reimbursement request; Management Authority; Intermediary Organism